Exploring the potential role of sonic hedgehog cell signalling pathway in antidepressant effects of nicotine in chronic unpredictable mild stress rat model. Issue 5 (May 2019) - Tayyab, Mohd; Shahi, Mehdi H.; Farheen, Shirin; Mariyath P.M., Mubeena; Khanam, Nabeela; Hossain, M. Mobarak
Abstract: Nicotine is the most common and highly addictive drug of abuse, associated with several life-threatening diseases and high mortality. Nicotine abuse is the concerted effort to feel reward and fight depression in depressed individuals. The underlying mechanism of nicotine is to activate the brain reward system in the central nervous system and provide an antidepressant effect. Antidepressants provide their therapeutic effect by stimulating hippocampal neurogenesis, which can be correlated with brain derived neurotrophic factor (BDNF) expression in the hippocampus. BDNF interacts with Wnt/β-catenin and sonic hedgehog (Shh) signalling cascade to stimulate hippocampal neurogenesis. Shh is the marker of hippocampal neurogenesis and also involved in the neuropathology of depression. But knowledge in this area to identify the potential therapeutic target is limited. In our study, we explored the role of BDNF, Wnt/β-catenin and Shh signalling in depression and the involvement of these signalling pathways in providing an antidepressant effect by nicotine. Our investigations showed that chronic unpredictable mild stress induced depression results declined expression of BDNF, Wnt/β-catenin, Shh and its downstream transcription factors GLI1/2/3 and NKX2.2 in the hippocampus of male Wistar rat. Moreover, we also observed that nicotine administration increased the expression of these signalling molecules in providing the antidepressant effects.